Outcomes of V‐cut Osteotomy on the First Metatarsal Head Combined with Fixation in Mortise‐shaped Bone Groove‐Plasty and Akin Osteotomy on the First Toe for Hallux Valgus Correction. Issue 11 (30th September 2022) - Jiao, Xin; Gan, Yaokai; Li, Yiming; Xu, Chen; Wang, Zengguang; Sun, Xin; Shi, Dingwei; Zhao, Jie; Dai, Kerong
Abstract : Objective: Hallux valgus (HV) is a common foot deformity, and recurrence is one of the most serious complications after HV correction. As a result, the surgical technique with a lower recurrence rate is a dream. The purpose of the article should be to observe the correction effect of hallux valgus using a novel "V‐cut" osteotomy on the first metatarsal head combined with fixation in mortise‐shaped bone groove‐plasty technique. Methods: Twenty‐three consecutive patients (40 feet) with HV were included from March 2019 to May 2020, who were all treated using single screw fixation with V‐cut osteotomy on the first metatarsal head combined with mortise‐shaped metatarsal bone groove‐plasty and Akin osteotomy on the first toe for hallux valgus correction. With a mean follow‐up time of 21.7 months, the visual analogue scale (VAS) score and American Orthopedic Foot and Ankle Society (AOFAS) forefoot score and the changes of the hallux valgus angle (HVA), intermetatarsal angle (IMA) and distal metatarsal articular angle (DMAA) were evaluated during the clinical follow‐up. The paired t test was used for analytical statistics. Results: The VAS score improved from 6.78 ± 1.74 to 1.87 ± 1.45 and the AOFAS score improved from 53.9 ± 12.3 preoperatively to 94.7 ± 6.8 in the latest follow‐up postoperatively ( P  < 0.01). Besides, the HVA improved from 30.0 ± 6.1° to 5.7 ± 2.8° ( P  < 0.01); the IMA changed from 13.1 ± 2.8° into 3.3 ± 1.6° ( P  < 0.01); and the DMAA ameliorated from 27.0 ± 8.4° to 5.9 ± 3.5° ( P  < 0.01). Only five toes had slight numbness and stiffness in early postoperative period, and these symptoms disappeared completely at 6 months after the surgery. Only one foot was corrected to excess. One screw stern protruding beneath the skin happened, which needed secondary screw removal under local anesthesia. Conclusions: Single screw fixation with V‐cut osteotomy on the first metatarsal head combined with fixation in mortise‐shaped metatarsal bone groove‐plasty and Akin osteotomy on the first toe is an effective way with low recurrence rate for HV correction. Abstract : A new way of osteotomy for hallux valgus was invented. The new treatment method had less complications.